EARLY PROTEROZOIC MAGMATIC BELT OF THE MOSCOW REGION - Bogdanova S.V.; Bibikova E.V.; Postnikov A.V.; Taran L.N. (My University, 2004)
The Moscow region is situated in the most complicated tectonic junction of the East European Craton (EEC), characterized by the intrusion of tectonic units of various orders and ages, such as the wedge of the Neoarchean Volga-Ural segment from the east, Neoarchean and Paleoproterozoic structures of the Fennoscandian segment from the north, and Meso- and Neoarchean tectonic units of the Sarmatian segment from the south. All of these EEC crustal segments have sharply distinct Archean and Paleoproterozoic histories and are divided in their present-day structure by early-middle Proterozoic transcratonic (Central Russian-Volyn-Orsha and Pachelma) rift segments that inherited the Paleoproterozoic Ryazan-Saratov (Pachelma) collisional belt (∼2 Ga) and Central Russian collisional belt (1.80-1.75 Ga).
Keywords: Proterozoic; Precambrian::Proterozoic; Докембрий::Протерозой